2010
DOI: 10.4049/jimmunol.0902383
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Promotes TLR4-Triggered Proinflammatory Mediator Production through Direct Estrogen Receptor α Signaling in Macrophages In Vivo

Abstract: 17β-estradiol (E2) has been shown to promote the expression of inflammatory mediators by LPS-activated tissue resident macrophages through estrogen receptor α (ERα) signaling. However, it remained to be determined whether E2 similarly influences macrophages effector functions under inflammatory conditions in vivo, and whether this action of E2 resulted from a direct effect on macrophages. We show in this study that chronic E2 administration to ovariectomized mice significantly increased both cytokine (IL-1β, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 33 publications
10
151
4
1
Order By: Relevance
“…7, A and B). Whereas in male mice, TLR4 activation is linked to myelopoiesis, Calippe et al (40) identified that estrogen signaling itself may influence TLR presence and activation state, and further studies have shown an effect of LPS responsiveness being reduced in females (41,42). These studies demonstrated that ER␣ activation itself stimulates TLR production of cytokines, priming the system for future dietary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…7, A and B). Whereas in male mice, TLR4 activation is linked to myelopoiesis, Calippe et al (40) identified that estrogen signaling itself may influence TLR presence and activation state, and further studies have shown an effect of LPS responsiveness being reduced in females (41,42). These studies demonstrated that ER␣ activation itself stimulates TLR production of cytokines, priming the system for future dietary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E 2 treatment of animals resulted in the inhibition of phosphoinositide kinase-3 (PI3K) activity and AKT phosphorylation in LPS-activated macrophages, whereas NF-kB p65 transcriptional activity was concomitantly increased. Further studies showed that targeted disruption of ERa gene in macrophages totally abolished the effect of E 2 on the expression of inflammatory mediators by peritoneal macrophages, thus indicating that E 2 directly targeted these cells to exert pro-inflammatory effects (Calippe et al 2010). The same group noticed that ERa-mediated signaling is required for optimal dendritic cell function as assessed by MHC-II and CD86 expression and pro-inflammatory cytokine production (IL6 and IL12) and that estrogens enhance susceptibility to experimental myasthenia gravis by augmenting dendritic cell activation and proinflammatory Th1 response (Delpy et al 2005, Douin-Echinard et al 2008.…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 98%
“…One of the bestdescribed endothelial actions of E 2 is stimulation of nitric oxide (NO) production, which depends on both genomic (expression of endothelial NO synthase (eNOS)) and nongenomic effects (activation of phosphatidylinositol 3-kinase and protein kinase AKT, phosphorylation of eNOS) (Arnal et al 2010, Chow et al 2010. Because the ability of E 2 to promote an increase in eNOS activity and NO-dependent vasorelaxation are abolished in ERa KO mice and are emulated by highly selective ERa agonists, modulation of NO production by E 2 is likely mediated by ERa (Arnal et al 2010, Bolego et al 2010. However, treatment of endothelial cells with E 2 also stimulates covalent adduction of a nitrosyl group to cysteins (S-nitrosylation), which represents a key route for NO to directly modulate protein functions and which depends on ERb (Zhang et al , 2012.…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, we do not know whether the influence of BPA on TLR-triggered cytokine response is a result of direct effect of BPA on TLR expression or the result of an indirect effect of BPA that disrupted downstream signaling events. Nevertheless, several experimental studies have shown that BPA can alter cytokine production via the P13K/Akt, the MAPK/AP-1, or the NF-κB pathways, whereas no influence was observed on TLR4 surface expression (21,24,25). The observation from our study that IL-10 response to TLR ligands remained unperturbed by BPA concentration might also give indirect evidence that BPA had no direct effect on TLR expression, because theoretically, all cytokine production would have been altered if TLR expression, being the origin of the signaling pathway, was modified.…”
Section: Discussionmentioning
confidence: 99%